Penerapan CBT (Competency Based Training ) Dalam Meningkatkan Prestasi Belajar Nilai dan Norma Sosial Pada Siswa Kelas X Ilmu Sosial 1 SMA Negeri 1 Sampara - Muna Muna (Gema Pendidikan, 2021)
Implementation of CBT (Competency Based Training) in Improving Learning Achievement of Social Values and Norms in Class X Social Sciences 1 SMA Negeri 1 Sampara Students "by Dra. Muna, M. Pd. The formulation of the problem is whether the application of the Competency Based Training learning approach can improve the learning achievement of social values and norms in class X Social Sciences 1 SMA Negeri 1 Sampara students? The data collection tools used were observation guidelines and tests for students. The findings in this study were that the Compotency Based Training learning approach could improve the learning achievement of class X Social Sciences 1 SMA Negeri 1 Sampara students on the subject matter of Social Values and Norms. Besides that, this approach can also increase students' knowledge about how to learn through observation and how to learn in groups. The recommendation of this research is that the CBT approach is one of the learning models that should be used in implementing learning in schools. This is done because the CBT approach can improve students' abilities and skills to learn together and solve problems faced together.